Microbial Community Composition of the Antarctic Ecosystems: Review of the Bacteria, Fungi, and Archaea Identified through an NGS-Based Metagenomics Approach - Vesselin V. Doytchinov; Svetoslav G. Dimov (Life, 2022)
Antarctica represents a unique environment, both due to the extreme meteorological and geological conditions that govern it and the relative isolation from human influences that have kept its environment largely undisturbed. However, recent trends in climate change dictate an unavoidable change in the global biodiversity as a whole, and pristine environments, such as Antarctica, allow us to study and monitor more closely the effects of the human impact. Additionally, due to its inaccessibility, Antarctica contains a plethora of yet uncultured and unidentified microorganisms with great potential for useful biological activities and production of metabolites, such as novel antibiotics, proteins, pigments, etc. In recent years, amplicon-based next-generation sequencing (NGS) has allowed for a fast and thorough examination of microbial communities to accelerate the efforts of unknown species identification. For these reasons, in this review, we present an overview of the archaea, bacteria, and fungi present on the Antarctic continent and the surrounding area (maritime Antarctica, sub-Antarctica, Southern Sea, etc.) that have recently been identified using amplicon-based NGS methods.